Effectiveness giving cookies Effect Of Moringa Oleifera Leaves On Increasing Hemoglobin Levels In Adolescent Girls At Private High School Pab 6 Helvetia Medan - Juliani, Sri; Sibero, Jitasari Tarigan; Wulan, Mayang; Fahra, Munawatun (Jurnal Maternitas Kebidanan, 2025)
Moringa leaf cookies are a food preparation from moringa leaves which contain many nutrients so that they can provide effectiveness for the hematopoiesis process, and the nutrients needed in the process of forming red blood cells so that they can overcome the decrease in hemoglobin levels in iron deficiency anemia for female adolescents. This study aims to determine the effect of giving moringa leaf cookies (moringa oleifera) on increasing hemoglobin levels in female adolescents at PAB 6 Private High School Helvetia Medan in 2025. The design of this study used a Quasi-Experiment with a one group pretest and posttest design. The population in this study were 16 female adolescents, the sampling technique in this study was total sampling where the number of samples equal to the number of population which were 16 respondents. Giving moringa leaf cookies were done for 7 consecutive days as many as 4 pieces in one day. Data analysis in this study used univariate and bivariate analysis. The bivariate analysis used was the paired T-Test. The results of the study showed the average hemoglobin level before the test was (12.2 g/dl) and the result after the test was (12.4 g/dl), with a difference of (0.2 g/dl). Based on the results of the paired sample t-test, a sig value of (0.000) < 0.05 was obtained, so it can be concluded that Ha is accepted. The conclusion in this study, there is an effect of giving moringa leaf cookies on increasing hemoglobin levels in female adolescents at PAB 6 Private High School Helvetia Medan. It is suggested that female adolescents can consume moringa leaf cookies as a non-pharmacological alternative to increase hemoglobin levels.